Distribution of light (LHREE) and heavy rare earth elements (HREE) in Kelantan granitoids rock. Issue 1 (August 2021) - Patah, M F A; Shafiee, N S; Ismail, R; Bahar, A M A; Khan, M M A; Eh Rak, A; Awang, M
Abstract: Peninsular Malaysia is being distributed into three parallel belts (Western, Central and Eastern). Kelantan is one of the states in Peninsular Malaysia and consider as a unique territory to have all three belts (Western, Central and Eastern). Each belts divided into several formations which are Western Belt (Main Range Granite), Central Belt (Jeli Granite, Kemahang Granite, Noring Granite, Kenerong Leucogranite, Berangkat Tonalite and Senting Granite) and Eastern Belt (Boundary Range Granite). Rare Earth Elements (REEs) are usually concentrated related to the alkaline – peralkaline, carbonalite igneous rocks, as well as sedimentary rocks. Granitoid and some intrusive volcanic rocks are widely exposed in Malaysia, as well as Kelantan state. REEs are relatively abundant in the Earth crust, however these elements are rarely concentrated in the mineable ore deposit. There are a lot of research about granitoids, but very limited studies about the distribution of the REE. The objective of this study is to investigate the distribution of REEs in different type of granitoid rocks in Kelantan. For this purpose, 15 samples were selected and analysed using Inductive Coupled Plasma Mass Spectrometry (ICP-MS). Result shows that, distribution of light REEs in all samples up to 78% and heavy REE up to 22% with total value 5350.69 ppm and 1491.27 ppm respectively. Surprisingly, Jeli Granite formation (LT15) is high potential of REE among the samples tested with total REE 3164.93 ppm and Kemahang Granite (JD18) is least potential with total REE 31.95 ppm. The granitoid distribution can be found widely in Kelantan with special characteristic and detailed study about mineral composition will help identifying the REE potential as well as generate more relatable study about genesis and nature of rocks in Malaysia.